Breakthrough of Lake Progress (East Antarctica): a phenomenological model and approaches to assessing the characteristics of a flash flood - G. V. Pryakhina; A. A. Chetverova; S. D. Grigorieva; A. S. Boronina; S. V. Popov (Лëд и снег)
On January 14, 2019, a breakthrough of water masses occurred on the Lake Progress (the oasis of the Larsemann hills, East Antarctica) with the formation of a flash flood. During the summer field seasons of the 63rd and 64th Russian Antarctic Expeditions (2017–2019), comprehensive hydrological, GPR and geodetic surveys were conducted in this area to ensure the safety of transport operations. The results of field measurements and calculations based on mathematical modeling of the breakthrough flood from the Lake are presented. The purpose of this study was to compare field observations and model calculations of the breakthrough flood and then to verify the existing model of Yu.B. Vinogradov on real data, since detailed observations of breakthrough floods of lakes of the Antarctic oases have not been previously carried out. The results of complex hydrological and geophysical investigations of LH73–Progress–Sibtorp lake system focused on areas where lake outburst are possible (snow-ice dams) made possible to formulate phenomenological model of the outburst process. It was emphasized that the lake water was discharged through a tunnel developed in the snow–ice dam, which subsequently evolved into a real riverbed. The maximum water discharge was formed approximately in 7.5 h after the start of the outflow, and it was estimated 5.4 m3s-1 according to the in-situ measurements, and 4.94 m3s-1 – by the model. The calculated volume of the flood is 76 320 m3. The differences between the model and in-situ measurements are about 9% that can be explained by the fact that the time of water retention by the snow-ice dam is not considered in the model.